Vitamin D Deficiency and Associated Factors in Adult Females of Chattogram (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background : Vitamin D is an essential nutrient and deficiency of it leads to devastating disorders. This study aimed to find out the associated factors with selected variables of low vitamin D among adult females of Chattogram.Materials and methods : Cross-sectional observational study was conducted from September 2019 to February 2020 at a diagnostic complex of Chattogram. Participants were adult females of Chattogram. All participants gave oral informed consent and answered a questionnaire that included 16 questions covering demographic information, monthly income, educational status, occupation, body weight, duration of sun exposure, dress pattern (Using hijab or burkha, regular dress-up) drug and disease history. Blood samples were collected by cautious aseptic procedure. Serum vitamin D levels were measured by using immunoassay method. Adult females of Chattogram with no religious restrictions, n= 150,aged 31 to 70 years.Results: Overall, 88% had low vitamin D levels with deficient 60.66% and insufficient 27.34%. Sufficient level of vitamin D was found only among 12%. The prevalence of vitamin D deficiency was much higher in females with house-wife status 73.33% (p value of 0.0001) wearing hijab 46.66% (p value of 0.001). It could be due to interference with UVB radiation into skin, short duration of sun exposure, use of sunblock cream or less supplementary intake.Conclusion : Vitamin D deficiency is an emerging but neglected health issue in modern time, particularly more vulnerable are female population. Ironically, abundant sunlight of Bangladesh seems failed to protect the self-imposed concrete prisoner, classically known as home-makers, and practitioner of indoor life style that leads to avoidance of sun light. However, large sample size is mandatory to boost-up the findings of current study.Chatt Maa Shi Hosp Med Coll J; Vol.20 (2); July 2021; Page 74-78